(untitled) (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2024)
How do we get children to move beyond the colonialist version of fantasy adventure to form a less self-centered and more nuanced version of what it means to be a hero? This article explores pressures on young Dungeons & Dragons players, urging Dungeon Masters (DMs) to foster empathy, cooperation, and critical thinking. By examining problematic tropes like "evil" races and antagonist cultures, the article highlights how these elements reflect colonialist ideology. Through anti-colonialist strategies – such as diverse narratives, respect-based norms, and safety tools like the "X card" – DMs can create games that emphasize moral complexity, helping players become empathetic individuals ready to challenge real-world inequalities.